SABDA AND DAWUH SRI SULTAN HBX ABOUT THE CROWN PRINCESS MAX WEBER’S STUDIES POWER, AUTHORITY, LEGITIMACY - Sigit Surahman,; Ahmad Sihabudin,; Fahrudin Faiz,; Ridzki Rinanto Sigit, (International Journal of Social Science, 2023)
This study discusses the proclamation and words (sabda and dawuh) of Sri Sultan Hamengkubuwono X (HBX) regarding the appointment of the Crown Princess. This study aims to investigate and analyze the power, authority, and legitimacy of the proclamation and statements of Sri Sultan HBX in the cultural context of the people of Yogyakarta. Max Weber's Theory of Power, Authority, and Legitimacy is used as a guide in conducting research. This study uses a qualitative approach with a focus on cultural perspectives involving Yogyakarta residents as the main source of information. The findings of this study contribute to a broader understanding of political, power and cultural dynamics in the context of the Sultanate of Yogyakarta